Kajian Model Trauma Healing Oleh Seorang Ayah Pada Anak Pasca Meninggalnya Ibu Rumah Tangga Di Lebbeng Mamuju - Prionaray Bram M; Alvin Ranteallo; Derry Vandya; Kerininda Pratiwi; Nadia Kristanti Podala; Radna Sambara; Lee Jhines; Winni Yunilta Padaungan (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
Death is an event that can have a traumatic impact on the family left behind. It is hoped that the peace process with oneself will come out of the traumatic period experienced. A healing process that has an impact also involves other people in resolving the trauma, using various trauma healing models. This aims to find out more about the trauma healing model using a play therapy approach. The method then used was a qualitative research method by taking a case study approach of the trauma felt by children due to the death of their lover's mother and a father who was required to be able to accompany his lover's children. This research will provide awareness to arrive at the ability to clearly find solutions and methods in overcoming perceived trauma.